Evolving Paradigms of Gender Inclusion: A Shift from Women in Development to Gender and Development (Patan Pragya, 2025)
This paper based on evolving paradigms of gender inclusion” refers to the shifting theoretical and policy frameworks that guide how societies understand and promote equitable participation of all genders. It captures the progression from women-centered approaches to more intersectional and structural models addressing power relations and systemic inequalities. The history of gender inclusion in development has been greatly conceptually and practically transformed to shift to the Gender and Development (GAD) paradigm as opposed to the Women in Development (WID) paradigm. This paper critically analyzes this historical path and how this has impacted on the current gender-equity policies and practices in Nepal. Developed in the 1970s, WID focused on including women into the prevalent developmental frameworks with its orientation on productive labour and significant disregard of structural inequalities, reproductive labour, and social-cultural limitations. The latter approach of Women and Development (WAD) offered a structural analysis, acknowledging both feminine household and economic roles of women with a focus on systemic subordination as a result of patriarchal and capitalism relations. AD took a relational and transformative approach by the 1980s, anticipating the gendering of power relations, institutional hierarchies and practices and suggesting interventions that could involve both men and women in dealing with substantive equity. These principles were operationalized into policy and planning strategies through such tools as the Moser Gender Planning Framework. The political involvement of women was limited by historical governance structure and other deep-rooted socio-cultural beliefs in Nepal. The 2015 changes in the legislation, provisions of the constitution, and quota systems have seen a significant rise in numerical representation, and women now hold almost 40% of the elected positions on the local level. However, there are still qualitative constraints: women are still left in junior or back-off positions, and the decision-making process in the executive position is male dominated. The conclusion of the study is that although the shift in WID-to-GAD has made women more visible and recognized by the institution, the true empowerment of women is achieved through structural inequities, social norms, and hierarchical power relations. This cannot be represented numerically and therefore transformative, context-sensitive approaches are needed to substantive gender equality in development.